Comprehensive analysis and insights gained from long-term experience of the Spanish DILI Registry - Stephens, Camilla; Robles-Díaz, María Mercedes; Medina-Cáliz, Inmaculada; García-Cortés, Miren; Ortega-Alonso, Aida; Sanabria-Cabrera, Judith Adriana; González-Jiménez, Andrés; Álvarez-Álvarez, Ismael; Slim, Mahmoud; Jiménez-Pérez, Miguel; González-Grande, Rocío; Fernández, M. Carmen; et al. (Elsevier, 2021)
Background & aims: Prospective drug-induced liver injury (DILI) registries are important sources of information on idiosyncratic DILI. We aimed to present a comprehensive analysis of 843 patients with DILI enrolled into the Spanish DILI Registry over a 20-year time period. Methods: Cases were identified, diagnosed and followed prospectively. Clinical features, drug information and outcome data were collected. Results: A total of 843 patients, with a mean age of 54 years (48% females), were enrolled up to 2018. Hepatocellular injury was associated with younger age (adjusted odds ratio [aOR] per year 0.983; 95% CI 0.974-0.991) and lower platelet count (aOR per unit 0.996; 95% CI 0.994-0.998). Anti-infectives were the most common causative drug class (40%). Liver-related mortality was more frequent in patients with hepatocellular damage aged ≥65 years (p = 0.0083) and in patients with underlying liver disease (p = 0.0221). Independent predictors of liver-related death/transplantation included nR-based hepatocellular injury, female sex, higher onset aspartate aminotransferase (AST) and bilirubin values. nR-based hepatocellular injury was not associated with 6-month overall mortality, for which comorbidity burden played a more important role. The prognostic capacity of Hy's law varied between causative agents. Empirical therapy (corticosteroids, ursodeoxycholic acid and MARS) was prescribed to 20% of patients. Drug-induced autoimmune hepatitis patients (26 cases) were mainly females (62%) with hepatocellular damage (92%), who more frequently received immunosuppressive therapy (58%).
Keywords: Hepatitis; Epidemiología; DILI; Hepatotoxicity; causative agents; drug-induced autoimmune hepatitis; epidemiology; outcome; risk factors; therapy in DILI